2019
DOI: 10.1002/open.201900189
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater To Resource: Design of a Sustainable Phosphorus Recovery System

Abstract: To enable a more sustainable wastewater treatment processes, a transition towards resource recovery methods that have minimal environmental impact while being financially viable is imperative. Phosphorus (P) is a finite resource that is being discharged into the aqueous environment in excessive quantities. As such, understanding the financial and environmental effectiveness of different approaches for removing and recovering P from wastewater streams is important to reduce the overall impact of wastewater trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This framework was applied to design, simulate and analyze the treatment pathways to select the most suitable methods for P removal and recovery. The results suggested that ion exchange had the best P selectivity (100% P-elimination) in terms of economic performance; chemical approach to P removal was the best, followed by ion exchange; biological methods had significantly higher associated costs per unit P removed with an inferior environmental performance [52].…”
Section: Current Practices To Recover Phosphate From Wastewater In Singaporementioning
confidence: 99%
“…This framework was applied to design, simulate and analyze the treatment pathways to select the most suitable methods for P removal and recovery. The results suggested that ion exchange had the best P selectivity (100% P-elimination) in terms of economic performance; chemical approach to P removal was the best, followed by ion exchange; biological methods had significantly higher associated costs per unit P removed with an inferior environmental performance [52].…”
Section: Current Practices To Recover Phosphate From Wastewater In Singaporementioning
confidence: 99%
“…Furthermore, when considering waste as a resource (as alluded to previously), the potential exists to unlock an otherwise untapped revenue stream, however this value is highly dependent on the available market for the specific component in question. Biofuels for example, have a well-established market, whereas the potential for a component such as phosphorus may be less clear [19]. The costs for discharging an unrecovered resource to the environment (environmental, financial or otherwise) may also prove critical.…”
Section: Current Status Of Resource Recovery From Wastewatermentioning
confidence: 99%
“…Apart from sustainability aspects, the increased processing costs for the achievement of even stricter disposal limits, as imposed by respective regulation norms to avoid potential environmental problems, usually require further potential exploitation of used end-of-life materials, such as phosphorus (P), to reduce the respective costs [2]. Phosphorus is among the important nutrients, pointing out the recycled/recovered options during each step of the wastewater treatment process due to its significance for the growth of plants and living organisms, as well as not being considered as a convenient renewable material in nature [3,4]. The crystallization of struvite (i.e., magnesium ammonium phosphate (MAP), MgNH 4 PO 4 •6H 2 O) during certain wastewater treatment processes, in regard to P-rich streams (usually after the anaerobic digestion of sludge), was once considered as a serious operational problem, but nowadays, it is mainly used to retrieve phosphorus from these streams when the existing conditions (i.e., mainly Mg and nutrients' content, pH, and temperature) allow for its formation, since it can be subsequently effectively applied as a potential fertilizer, therefore enabling the recovery of phosphorus from wastewaters and its environmental reuse [5,6].…”
Section: Introductionmentioning
confidence: 99%